Antecedents and consequences of mutual trust in PPPs - Panchapakesan, P.; Rosa, A.; António, N. (Journal of Relationship Marketing, 2017)
This article aims to identify the antecedents and consequences of mutual trust in public-private partnerships (PPPs), making use of the theory of mutual trust to develop the conceptual model. The article then tests hypotheses to find the role of trust in PPPs and also to identify the antecedents and consequences. Data have been collected from personnel working in government, corporate and non-profit sectors related to a post-earthquake psychological rehabilitation program in China. A total of 234 usable responses have been obtained with a return rate of 69.2%. The results of structural equation modeling show that while mutual communication, corporate reputation, and shared value influence mutual trust between partners positively, opportunism exerts negative influence on trust; in addition, trust also influences performance, commitment, and long-term relationships between partners. We conclude that mutual trust eliminates opportunism and increases confidence between partners, leading to improved inter-firm performance. If the partners establish trust in the PPP, they reap all other benefits of cooperation of PPPs.